Recycling spent mushroom substrate into fuel pellets for low-emission bioenergy producing systems - Alves, Lucas da Silva [UNESP]; Moreira, Bruno Rafael de Almeida [UNESP]; Viana, Ronaldo da Silva [UNESP]; Pardo-Gimenez, Arturo; Dias, Eustáquio Souza; Noble, Ralph; Zied, Diego Cunha [UNESP] (Elsevier, 2021)
This study aimed at analyzing the feasibility of converting diverse types of spent mushroom substrate (SMS) into fuel pellets for low-emission bioenergy producing systems. Sources of SMS for pelletization included paddy straw and achiote capsule shell from Pleurotus ostreatus, eucalyptus sawdust and grassy straw from Lentinula edodes, and compost with either peat or soil as a casing layer from Agaricus subrufescens. The pilot-scale manufacturing of fuel pellets consisted of compacting the feedstocks in an automatic pelletizer machine at 200 MPa and 125 °C. Pellets from SMS, irrespective of source, met the international standards for solid biofuels, except for ash content. However, due to moderate sulfur content (0.05%), they tended to low slagging (S < 0.60) and intermediate fouling (0.60 ≤ F ≤ 40.00) on a boiler's heating surface. Because of the significant ash content of 29.10–31.80%, these products resisted oxidation more at the onset of combustion, burned themselves out gradually and conducted 2.70–2.90 W g−1 heat at around 300 °C. Pellets of SMS from A. subrufescens grown on compost with soil casing, produced less heat (4.25 W g−1) than reference pellets from pinewood sawdust (5.10 W g−1), but emitted less CO2 (7.50 ppb vs 15.10 ppb), NOx (130.10 ppt vs 147.90 ppt), SO2 (3.15 ppt vs 16.70 ppt), and volatile organic compounds (17.65 mg m−3 vs 27.20 mg m−3). Pelletization of SMSs valorized these agro-food residues via waste-to-energy pathways towards a circular economy. SMS from A. subrufescens grown on compost with soil casing had the best properties for high-performance pelletization.
Keywords: Agro-food residue; Circular economy; Commercially valuable edible fungi; Energy biomass; Low-carbon society; Sustainable waste-to-energy technology